2016
DOI: 10.1586/17476348.2016.1133304
|View full text |Cite
|
Sign up to set email alerts
|

Addressing corticosteroid insensitivity in adults with asthma

Abstract: Corticosteroids are the most effective treatment for asthma, but the therapeutic response varies markedly between individuals, with up to one third of patients showing evidence of insensitivity to corticosteroids. This article summarizes information on genetic, environmental and asthma-related factors as well as demographic and pharmacokinetic variables associated with corticosteroid insensitivity in asthma. Molecular mechanisms proposed to explain corticosteroid insensitivity are reviewed including alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 165 publications
0
9
0
Order By: Relevance
“…Corticosteroid insensitivity occurs in chronic inflammatory diseases including severe asthma and COPD [53,54]. The effects of budesonide on epithelial barrier function in primary bronchial epithelial cells is impaired in asthma and COPD, and this effect is less evident in healthy smokers, suggesting that corticosteroid responsiveness in smokers without spirometric evidence of COPD might be better preserved than in those with COPD [55], although this hypothesis remains to be tested in clinical studies.…”
Section: Corticosteroid Insensitivitymentioning
confidence: 99%
“…Corticosteroid insensitivity occurs in chronic inflammatory diseases including severe asthma and COPD [53,54]. The effects of budesonide on epithelial barrier function in primary bronchial epithelial cells is impaired in asthma and COPD, and this effect is less evident in healthy smokers, suggesting that corticosteroid responsiveness in smokers without spirometric evidence of COPD might be better preserved than in those with COPD [55], although this hypothesis remains to be tested in clinical studies.…”
Section: Corticosteroid Insensitivitymentioning
confidence: 99%
“…In humans, about 10-20 % of patients with inflammatory diseases and immune disorders do not respond to treatment with glucocorticoids (59). In addition, corticosteroid insensitivity (i.e., an impaired response to corticosteroids) in asthma in humans is a well-recognized phenomenon, and it has been estimated that corticosteroid insensitivity is present in about one third of asthma patients (60). We are not aware of any published reports regarding the prevalence of corticosteroid resistance or insensitivity in horses.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids stop the process of airway remodeling by inhibiting the metaplasia of goblet cells, the hypertrophy and phenotypic transition of ASM cells, the proliferation of lung fibroblasts, the release of inflammatory mediators, and the thickening of the subepithelial RBM and by repairing the epithelial layer (43)(44)(45). However, up to 1/3 of asthma patients are clinically insensitive to glucocorticoid therapy (46) for which airway remodeling may play an important role. Bourdin et al (47) found that a limited steroid response to short-acting glucocorticoids in severe asthma was associated with the thickening of bronchial basement membrane, and that RBM thickness could predict steroid responsiveness below 15%.…”
Section: Glucocorticoid Therapymentioning
confidence: 99%